Agriculture, food, and nutrition interventions that facilitate sustainable food production and impact health: an overview of systematic reviews - Michelle M. Haby; Evelina Chapman; Rachel Clark; Luiz A.C. Galvão
ABSTRACT Objectives To identify the agriculture, food, and nutrition security interventions that facilitate sustainable food production and have a positive impact on health. Methods Systematic review methods were used to synthesize evidence from multiple systematic reviews and economic evaluations through a comprehensive search of 17 databases and 10 websites. The search employed a pre-defined protocol with clear inclusion criteria. Both grey and peer-reviewed literature published in English, Spanish, and Portuguese between 1 January 1997 and November 2013 were included. To classify as "sustainable," interventions needed to aim to positively impact at least two dimensions of the integrated framework for sustainable development and include measures of health impact. Results Fifteen systematic reviews and seven economic evaluations met the inclusion criteria. All interventions had some impact on health or on risk factors for health outcomes, except those related to genetically modified foods. Impact on health inequalities was rarely measured. All interventions with economic evaluations were very cost-effective, had cost savings, or net benefits. In addition to impacting health (inclusive social development), all interventions had the potential to impact on inclusive economic development, and some, on environmental sustainability, though these effects were rarely assessed. Conclusions What is needed now is careful implementation of interventions with expected positive health impacts but with concurrent, rigorous evaluation. Possible impact on health inequalities needs to be considered and measured by future primary studies and systematic reviews, as does impact of interventions on all dimensions of sustainable development.